Improving knowledge capture during conceptual design phase of building projects - Pourzolfaghar, Zohreh (2011)
Incomplete knowledge flow between architects and mechanical/electrical engineers engenders huge expense and untimely delivery of building projects. It is essential to consider mechanical electrical requirements from the early stages of design; and many experienced architects acknowledge this knowledge entities and the necessity for considering them at the right time.Therefore, inefficient knowledge flow among professionals during architectural conceptual design is emphasized as a problem for this study. For overcoming this problem, the study intends to improve knowledge capture during conceptual design phase of building project by formalizing the fundamental requirements of necessary mechanical/electrical knowledge. During this phase. To achieve this goal, this research develop three objectives: 1) Specify an appropriate knowledge capture technique for tacit dominated conceptual design phase; 20 Identify fundamental mechanical/electrical requirement to consider by architects during conceptual design phase and 3) Develop a framework for formalizing tacit mechanical/electrical knowledge during conceptual design phase. Firstly, the study selects an appropriate technique to capture expert’s tacit based on a literature survey by matching existing knowledge capture techniques with conceptual design characteristics. Secondly mechanical/electrical knowledge is obtained through a case study during conceptual design of a green building project. The mechanical/electrical knowledge and activities are matched in the McMillan Framework (2001) for the conceptual design phase. Later, mechanical/electrical knowledge is matched and assigned to the architectural concept design activities. At the conclusion of the exercise, the study developed a mechanical/electrical knowledge-based framework for the conceptual design phase. Validation of the result was obtained by using computational organizational theory simulation. This study contributes in extending McMillan’s Framework to include explicit fundamental required mechanical/electrical knowledge during the conceptual design phase; developing a tacit knowledge capture technique by combining tacit observation and explicit repertory grid documentation; and improving Nissen’s (2006) multidimensional model (MDM) by integrating knowledge into Macmillan’s framework for conceptual design activities. These results support the need to mitigate potential knowledge losses in tacit-dominant area between experts during conceptual design phase of building projects.